Design and construction of prototype color quinoa sorting machine using IR sensors - Chagua Aduviri, Irenio Luis (2022)
Quinoa (Chenopodium quinoa) is one of the main grains of a domesticated species native to the high Andean plains and valleys. Because its harvests do not always have a homogeneous color, some companies have been using sorting machines for quinoa that are adapted from other cereals, whose operation does not guarantee the desired efficiency. The purpose of the study was to design and build a prototype machine that classifies quinoa grains according to the desired color. The main parts of the machine include the design of the mechanical structure comprising three zones: feeding, transport and processing and storage. The parts were built with steel materials and some parts with PLA filament manufactured with 3D printer; electronic control system, using a microcontroller for adapting the IR sensor signal and controlling the electro actuators for the selection of homogeneous quinoa according to the allowed color parameters; and mechanical operation control, using two motors, one for the dosing of quinoa grains and the other for the movement of the conveyor belt. To achieve the best performance, adjustments were made regarding the speed and quantity of quinoa, establishing 24 rows with an elevation of 22 degrees with respect to the horizontal axis, having achieved the goal of 5 kg per hour and obtained the homogeneity of quinoa grains with high efficiency and better quality for marketing.